The Case of the Cat with the Missing Ear - Scott Emerson (United States Simon & Schuster Books for Young Readers)
"And if I'm not mistaken," said Blackthorne, peering into the microscope, "we can narrow down our list of Mr. Kirkpatrick's visitors to a dalmatian, a Sussex spaniel, a poodle, a weimaraner..." -- Blackthorne looked up from the microscope -- "and an orange-haired cat." Samuel Blackthorne, a Yorkshire terrier, is a master of observation and a genius of deductive reasoning who earns his living by unraveling mysteries and solving crimes. When Molly Kirkpatrick, a sleek greyhound, comes to Blackthorne for help in finding her missing brother Patrick, a quiet accountant, it seems like a simple enough case. But the trail leads Blackthorne and his colleague, Smithfield, to the docks, the dog track, casinos, and all kinds of roguish characters. They are caught up in an increasingly convoluted web of deceit that involves the highest-ranking officials in the city -- and a mysterious, possibly deadly, cat with just one ear. In this witty mystery Scott Emerson recounts the amazing adventures of Mr. Samue...
Keywords: Mystery